Amelioration of acute myocardial infarction injury through targeted ferritin nanocages loaded with an ALKBH5 inhibitor. (1st March 2022) - Cheng, Panke; Han, Hukui; Chen, Fuli; Cheng, Lianying; Ma, Cui; Huang, Hui; Chen, Chi; Li, Hua; Cai, Hao; Huang, Hao; Li, Gang; Tao, Jianhong
Abstract: The roles of m 6 A RNA methylation and mitochondrial metabolism in acute myocardial infarction (AMI) remain unclear. In this study, we demonstrated that m 6 A RNA methylation affected ischemia/reperfusion (I/R) injury in AMI through the "Erasers" protein ALKBH5-related metabolic reprogramming, characterized by the inhibition of enzyme activities of the tricarboxylic acid cycle; moreover, a surface-modified bioengineered ferritin nanocage was obtained from Archaeoglobus fulgidus, with a chimeric structure containing 8 lysine residues, SpyTag/SpyCatcher, and the C1q ligand Scarf1, which could disassemble and self-assemble in neutral solutions according to different Mg 2+ concentrations. The surface-modified bioengineered ferritin nanocage targeted the dying cells in the infarct area under the guidance of Scarf1. These cells were then phagocytosed through recognition of their TfR1 receptor. Lysosomal escape was achieved through the 8 lysine residues on the nanocage, and the nanocage disassembled based on the differences in intracellular and extracellular Mg 2+ concentrations. Finally, the ALKBH5 inhibitor IOX1 was loaded onto the ferritin nanocage and used in the AMI model, and it was found to effectively improve cardiac function. These results provide a potential strategy for the treatment of AMI in the future. Statement of significance: In acute myocardial infarction (AMI) induced by ischemia/reperfusion injury, m 6 A RNA methylation aggravates the injury through the "Erasers" protein ALKBH5-related metabolic reprogramming. To achieve precise treatment, genetic engineering-based recombinant expression technology was used to obtain a ferritin from Archaeoglobus fulgidus . The obtained ferritin was designated as HAfFtO, and it can disassemble and self-assemble in a neutral solution under different Mg 2+ concentrations and achieve lysosomal escape. Three G4S linkers were used to connect SpyTag with HAfFtO to synthesize HAfFtO-ST and recombination Scarf1 containing SpyCatcher structure, namely SC-Sf. According to the SpyTag/SpyCatcher technique, HAfFtO-ST and SC-Sf can form a gentle and firm combination, namely HSSS. The ALKBH5 inhibitor IOX1 was loaded on HSSS to form HSSS-I. HSSS-I effectively improved the cardiac function and decreased the infarct size in AMI. Graphical abstract: Image, graphical abstract